Construction and validation of a scale for assessing critical social justice attitudes - Lahtinen, Oskari (Wiley-Blackwell, 2025)
Two large studies (combined n = 5,878) set out to construct and validate a scale for assessing critical social justice attitudes. Studies assessed the reliability, factor structure, model fit, and both convergent and divergent validity of the scale. Studies also examined the prevalence of critical social justice attitudes in different populations and the scale's correlations with other variables of interest, including well-being variables: anxiety, depression, and happiness. Participants for Study 1 (n = 848) were university faculty and students, as well as non-academic adults, from Finland. Participants responded to a survey about critical social justice attitudes. Twenty one candidate items were devised for an initial item pool, on which factor analyses were conducted, resulting in a 10-item pilot version of critical social justice attitude scales (CSJAS). Participants for Study 2 were a nationwide sample (n = 5,030) aged 15–84 from Finland. Five new candidate items were introduced, of which two were included in the final, seven-item, version of CSJAS. The final CSJAS scale had high reliability (α = 0.87, ω = 0.88) and a good model fit (comparative fit index [CFI] = 0.99, TLI = 0.99, root mean square error of approximation [RMSEA] = 0.04, standardized root mean residual [SRMR] = 0.01, χ2 (14, 5024) = 132.8 (p < 0.001)) as well as convergent and divergent validity. Overall, the study sample rejected critical social justice propositions, with strong rejection from men. Women expressed more than twice as much support for the propositions (d = 1.20). In both studies, CSJAS was correlated with depression, anxiety, and (lack of) happiness, but not more so than being on the political left was. The critical social justice attitude scale was successfully constructed and validated. It had good reliability and model fit.